All-solid-waste high-ductility low-shrinkage geopolymer concrete material and preparation method thereof

By using coal-based solid waste polymer gelling material and PVA fibers, combined with shrinkage agent, high ductility and low shrinkage polymer concrete is prepared, which solves the problem of concrete cracking during bending and deformation, and achieves low carbon Efficient preparation of concrete materials.

CN119430769APending Publication Date: 2025-02-14TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411681377.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing concrete materials are prone to cracking when bending and deforming, showing brittleness, resulting in poor structural service performance, and the use of cement in traditional high-ductility concrete during the preparation process leads to high carbon emissions.

Method used

Coal-based solid waste polymer gelling materials are prepared by coal gangue powder and fly ash, combined with coal gangue fine aggregate and regenerated fine aggregate, mixed with PVA fiber and different shrinkage agents, and prepared high ductility and low ductility through performance optimization design. Shrinked polyconcrete.

Benefits of technology

The preparation of high-ductility and low-shrinkage concrete has been achieved, the service performance of bent components and road and bridge concrete has been improved, the number of maintenance times during service has been reduced, carbon emissions have been reduced, and the cost has been lower.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430769A_ABST
    Figure CN119430769A_ABST
Patent Text Reader

Abstract

The invention relates to high-valued resource utilization of solid wastes in the field of buildings, in particular to an all-solid-waste high-ductility low-shrinkage geopolymer concrete material and a preparation method thereof. Comprising the following raw materials in parts by mass: 615 to 1230 parts of coal gangue powder, 0 to 615 parts of fly ash, 123 to 492 parts of an alkali activator, 369 to 443 parts of fine aggregate, 24.6 to 98.4 parts of a shrinkage reducing agent, 12.3 to 24.6 parts of a water reducing agent, 6.15 to 12.3 parts of hydroxypropyl methyl cellulose, 369 to 418 parts of water and 19.5 to 26 parts of fibers. The concrete developed by the invention integrates high ductility, low shrinkage and strength grade not lower than C35, can be used for pouring and repairing flexural members and road and bridge deck concrete in the civil engineering field, reduces the maintenance frequency of the members, prolongs the service life of the structure, and reduces the maintenance cost; and moreover, resource high-value utilization of industrial solid waste and building solid waste can be realized, and carbon emission is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to high-value resource utilization of solid waste in the field of construction, and in particular to an all-solid waste high-ductility low-shrinkage geopolymer concrete material and a preparation method thereof. Background Art

[0002] With the rapid development of my country's construction and transportation industries, high quality and high durability requirements have been put forward for the service performance of concrete materials. Concrete is mainly used for bending members and road and bridge pavement layers in the field of civil engineering in my country. Concrete is prone to cracking when subjected to bending and tensile deformation during service, showing obvious brittle characteristics, which seriously affects the normal use of the structure during service. For cracked concrete bending members, surface reinforcement such as epoxy resin and cement mortar or removal of old concrete and pouring new concrete are used to solve the problem. For cracked concrete on road and bridge decks, high-performance concrete materials with the same or higher strength grade as the original road and bridge deck materials are generally used for repair. Brittle materials are still used to repair concrete cracks. This repair method only treats the symptoms and not the root cause, and cannot fundamentally solve the problem of brittle cracking of concrete. In order to reduce the cracking problem caused by the poor bending and tensile deformation capacity of brittle concrete, a high-ductility concrete material with good bending and tensile deformation capacity is required for pouring or repairing.

[0003] At present, traditional high-ductility concrete is made of cement, mineral admixtures, fine aggregates, fibers and admixtures as raw materials. The ultimate elongation under axial tension is not less than 0.5% and the average crack width is not more than 200μm. Since there is no coarse aggregate in high-ductility concrete, the drying shrinkage is at least 1200με, while the drying shrinkage of ordinary concrete is generally 600με. Large drying shrinkage will cause tensile stress inside the concrete, leading to concrete cracking. Therefore, in order to reduce the cracking caused by drying shrinkage, a high-ductility and low-shrinkage concrete material needs to be prepared. Cement is a hydraulic cementitious material with high carbon emissions. The use of cement to prepare high-ductility concrete is not conducive to the implementation of the dual carbon policy. Geopolymers can be prepared by using strong alkaline solution as an alkaline activator to activate coal-based solid waste. Using geopolymers instead of cement as a cementitious material to prepare concrete can reduce carbon emissions. Industrial solid waste coal gangue and construction solid waste can be crushed into fine aggregates to replace natural resources river sand and reduce natural resource mining.

[0004] The current status of research on the use of geopolymer cementitious materials to prepare high ductility concrete is shown in Table 1. As can be seen from Table 1, slag, fly ash, and silica fume are usually used as precursor materials, and geopolymers are prepared by stimulating their activity with sodium hydroxide and water glass. Aggregates mainly use river sand, reclaimed sand, and quartz sand. High ductility geopolymer concrete is prepared by adding polyethylene (PE) fiber and PVA fiber. However, low shrinkage is not involved; and the ultimate tensile strength and elongation of PE fiber are higher than those of PVA fiber. The design theory of preparing ultra-high ductility concrete with PE fiber is different from the design theory of preparing high ductility concrete with PVA fiber; in addition, the cost of PE fiber is significantly higher than that of PVA fiber, resulting in the cost of ultra-high ductility concrete being greater than the cost of high ductility concrete, which is not conducive to the promotion and application of PE fiber.

[0005] Table 1 Comparison of the current status of research on invention patents related to high ductility geopolymer concrete

[0006]

[0007] The current research status on the preparation of high ductility and low shrinkage concrete using different shrinkage reducers is shown in Table 2. Porous materials, calcium sulfoaluminate expansion agents and shrinkage reducers are usually used to reduce the shrinkage of high ductility concrete, but the ultimate elongation of high ductility concrete after uniaxial tension is not involved.

[0008] Table 2 Comparison of the current status of research on invention patents related to high ductility and low shrinkage concrete

[0009] Summary of the invention

[0010] The present invention overcomes the shortcomings of the prior art and provides a fully solid waste high ductility low shrinkage geopolymer concrete material and a preparation method thereof. Different from the technologies in Table 1 and Table 2, the present invention uses coal gangue powder and fly ash to prepare coal-based solid waste geopolymer cementitious materials, uses coal gangue fine aggregate and recycled fine aggregate, adds different shrinkage reducing agents, uses PVA fibers to play a fiber bridging role, and prepares high ductility low shrinkage geopolymer concrete through performance optimization design, which can not only realize the high-value utilization of solid waste resources, but also improve the service performance of bending components and road and bridge deck concrete, reduce the number of maintenance times during the service period, and increase the service life of the structure.

[0011] Based on the micromechanical design theory of high-ductility concrete, the ultimate elongation of high-ductility concrete is related to the matrix properties, fiber properties, and the matrix-fiber interface bonding properties. Compared with high-ductility concrete, the matrix strength of high-ductility low-shrinkage geopolymer concrete is high and the shrinkage deformation is small. When the fiber plays a bridging role and is pulled out of the matrix, it is difficult to pull out the fiber due to the small shrinkage of the matrix, which weakens the fiber bridging ability and thus affects the ultimate elongation of high-ductility low-shrinkage geopolymer concrete. The strength of coal gangue fine aggregate and recycled fine aggregate is lower than that of river sand. The use of coal gangue fine aggregate and recycled fine aggregate to prepare high-ductility low-shrinkage geopolymer concrete will weaken its strength. Therefore, how to balance the low shrinkage, high ductility and strength of high-ductility low-shrinkage geopolymer concrete is the difficulty and innovation of the patent of this invention.

[0012] In order to solve the above technical problems, the technical solution adopted by the present invention is: a full-solid waste high-ductility and low-shrinkage geopolymer concrete material, comprising the following raw materials in proportion by weight: 615-1230 parts of coal gangue powder, 0-615 parts of fly ash, 123-492 parts of alkali activator, 369-443 parts of fine aggregate, 24.6-98.4 parts of shrinkage reducer, 12.3-24.6 parts of water reducer, 6.15-12.3 parts of hydroxypropyl methylcellulose, 369-418 parts of water, and 19.5-26 parts of fiber.

[0013] As a further limitation of the technical solution of the present invention, the specific surface area of ​​the coal gangue powder and fly ash is not less than 664m 2 / kg, the basic particle size is 0.7-40μm; the total mass content of aluminum oxide and silicon oxide in the coal gangue powder and fly ash is not less than 90%.

[0014] As a further limitation of the technical solution of the present invention, the alkaline activator is one or a combination of water glass and sodium hydroxide; when the alkaline activator is a combination of water glass and sodium hydroxide, the modulus of the water glass is 1.8 to 3.3.

[0015] As a further limitation of the technical solution of the present invention, the fine aggregate is one of coal gangue fine aggregate and recycled fine aggregate or a combination thereof, the maximum particle size of the fine aggregate is 1.18 mm, and the fineness modulus is 1.36-1.58.

[0016] As a further limitation of the technical solution of the present invention, the shrinkage reducer is one or a combination of ethylene glycol diethyl ether liquid shrinkage reducer and ettringite expansion agent.

[0017] As a further limitation of the technical solution of the present invention, the fiber is polyvinyl alcohol (PVA) fiber with a diameter of 25-40 μm, a length of 8-12 mm, an elastic modulus of 34-36 GPa, a tensile strength of at least 1200 MPa, and an ultimate elongation of 9-12%.

[0018] The present invention also provides a method for preparing the above-mentioned all-solid waste high-ductility and low-shrinkage geopolymer concrete material, comprising the following steps:

[0019] 1) The gangue powder and fly ash are slowly stirred in a mixer for 1 to 2 minutes, with the rotation speed of 140 rpm and the revolution speed of 62 rpm;

[0020] 2) Add the alkaline activator and water into a mixer and stir rapidly for 3 to 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0021] 3) Add fine aggregate, shrinkage reducing agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 3 to 4 minutes, that is, the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0022] 4) Add the fiber and stir rapidly for 2 to 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0023] 5) Assemble the mold, remove the mold after curing in a standard curing box for 24 hours, and test the deformation performance, compressive strength and tensile properties.

[0024] As a further limitation of the technical solution of the present invention, the following steps are included: the entire process of preparation steps 1), 2), 3) and 4) takes 9 to 13 minutes.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) Compared with the prior art, the present invention has the characteristics of high ductility, low shrinkage and strength grade not lower than C35, and can provide an effective method for pouring or repairing concrete of bending members and road and bridge decks.

[0027] 2) In terms of economic benefits, all-solid waste high-ductility and low-shrinkage geopolymer concrete uses low-cost solid waste and has excellent performance. When used for pouring concrete for flexural members and road and bridge decks, it can increase the service life, reduce the number of maintenance times, and improve the economic benefits of the project.

[0028] 3) In terms of social benefits, the use of all-solid waste high-ductility, low-shrinkage geopolymer concrete in the pouring or repair of flexural components and road and bridge deck concrete can increase the design life of components, reduce the frequency of maintenance, and thereby reduce the noise caused by the demolition of cracked concrete and the noise during pouring, thereby improving human living standards.

[0029] 4) In terms of ecological benefits, under the concept of low-carbon sustainable development, coal gangue powder and fly ash are used to prepare coal-based solid waste geopolymers, and coal gangue fine aggregate and recycled fine aggregate are used to prepare all-solid waste high-ductility and low-shrinkage geopolymer concrete through performance optimization design. This can not only realize the resource and high-value utilization of bulk industrial solid waste and construction solid waste, but also replace high-carbon emission cement and promote dual carbon actions. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the uniaxial tensile stress-strain relationship curve of the high ductility and low shrinkage geopolymer concrete material prepared in Examples 1 to 5 and the comparative example.

[0031] Figure 2 It is the deformation performance curve of the all-solid waste high ductility and low shrinkage geopolymer concrete material prepared in Examples 1 to 5. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments.

[0033] Example 1

[0034] The material mix ratio of the all-solid waste high-ductility low-shrinkage geopolymer concrete in this embodiment is shown in Table 3.

[0035] Table 3 Material Proportion (Mass Ratio)

[0036]

[0037] The fineness modulus of the above-mentioned coal gangue fine aggregate and recycled fine aggregate is 1.36, the PVA fiber length is 12 mm, the elastic modulus is 36 GPa, the tensile strength is 1200 MPa, and the ultimate elongation is 9%.

[0038] The preparation steps are as follows:

[0039] 1) The gangue powder and fly ash are slowly stirred in a mixer for 2 minutes, with the rotation speed of 140 rpm and the revolution speed of 62 rpm;

[0040] 2) adding sodium hydroxide and water as an alkaline activator into a mixer and rapidly stirring for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0041] 3) Add fine aggregate, shrinkage reducing agent, expansion agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0042] 4) Add the fiber and stir rapidly for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0043] 5) Assemble the molds, and remove the molds after curing in a standard curing box for 24 hours. Test the shrinkage performance after curing for 1 day to 180 days, and the compressive strength and tensile properties after curing for 28 days.

[0044] The entire process of preparation steps 1), 2), 3) and 4) takes 12 minutes.

[0045] Example 2

[0046] The material mix ratio of the all-solid waste high-ductility low-shrinkage geopolymer concrete in this embodiment is shown in Table 4.

[0047] Table 4 Material Proportion (Mass Ratio)

[0048]

[0049] The modulus of the water glass is 1.8, the fineness modulus of the coal gangue fine aggregate is 1.39, the length of the PVA fiber is 8 mm, the elastic modulus is 35.4 GPa, the tensile strength is 1250 MPa, and the ultimate elongation is 9.5%.

[0050] The preparation steps are as follows:

[0051] 1) Add coal gangue powder, alkali activator and water into a mixer and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0052] 2) adding coal gangue fine aggregate, water glass, water reducing agent and hydroxypropyl methylcellulose and stirring rapidly for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0053] 3) Add the fiber and stir rapidly for 2 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0054] 4) Assemble the molds, and remove the molds after curing in a standard curing box for 24 hours. Test the shrinkage performance after curing for 1 day to 180 days, and the compressive strength and tensile properties after curing for 28 days.

[0055] The entire process of preparation steps 1), 2) and 3) takes 9 minutes.

[0056] Example 3

[0057] The material mix ratio of the all-solid waste high-ductility low-shrinkage geopolymer concrete in this embodiment is shown in Table 5.

[0058] Table 5 Material Proportion (Mass Ratio)

[0059]

[0060] The above-mentioned water glass modulus is 3.3, the fineness modulus of the recycled fine aggregate is 1.58, the PVA fiber length is 10 mm, the elastic modulus is 34 GPa, the tensile strength is 1350 MPa, and the ultimate elongation is 11%.

[0061] The preparation steps are as follows:

[0062] 1) The gangue powder and fly ash are slowly stirred in a mixer for 1 minute, with the rotation speed of 140 rpm and the revolution speed of 62 rpm;

[0063] 2) Add the alkaline activator and water into a blender and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0064] 3) Add recycled fine aggregate, shrinkage reducing agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0065] 4) Add the fiber and stir rapidly for 2 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0066] 5) Assemble the molds, and remove the molds after curing in a standard curing box for 24 hours. Test the shrinkage performance after curing for 1 day to 180 days, and the compressive strength and tensile properties after curing for 28 days.

[0067] The entire process of preparation steps 1), 2), 3) and 4) takes 10 minutes.

[0068] Example 4

[0069] The material mix ratio of the all-solid waste high-ductility low-shrinkage geopolymer concrete in this embodiment is shown in Table 6.

[0070] Table 6 Material Proportion (Mass Ratio)

[0071]

[0072] The modulus of the water glass is 3.0, the fineness modulus of the gangue fine aggregate and the recycled fine aggregate is 1.51, the length of the PVA fiber is 12 mm, the elastic modulus is 35.8 GPa, the tensile strength is 1380 MPa, and the ultimate elongation is 12%.

[0073] The preparation steps are as follows:

[0074] 1) The gangue powder and fly ash are slowly stirred in a mixer for 2 minutes, with the rotation speed of 140 rpm and the revolution speed of 62 rpm;

[0075] 2) Add the alkaline activator and water into a blender and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0076] 3) Add fine aggregate, shrinkage reducing agent, expansion agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0077] 4) Add the fiber and stir rapidly for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0078] 5) Assemble the molds, and remove the molds after curing in a standard curing box for 24 hours. Test the shrinkage performance after curing for 1 day to 180 days, and the compressive strength and tensile properties after curing for 28 days.

[0079] The entire process of preparation steps 1), 2), 3) and 4) takes 13 minutes.

[0080] Example 5

[0081] The material mix ratio of the all-solid waste high-ductility low-shrinkage geopolymer concrete in this embodiment is shown in Table 7.

[0082] Table 7 Material Proportion (Mass Ratio)

[0083]

[0084] The modulus of the water glass is 2.5, the fineness modulus of the gangue fine aggregate and the recycled fine aggregate is 1.44, the length of the PVA fiber is 10 mm, the elastic modulus is 34.7 GPa, the tensile strength is 1270 MPa, and the ultimate elongation is 11.2%.

[0085] The preparation steps are as follows:

[0086] 1) The gangue powder and fly ash are slowly stirred in a mixer for 1 minute, with the rotation speed of 140 rpm and the revolution speed of 62 rpm;

[0087] 2) Add the alkaline activator and water into a blender and stir rapidly for 4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0088] 3) Add fine aggregate, shrinkage reducing agent, expansion agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0089] 4) Add the fiber and stir rapidly for 2 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm;

[0090] 5) Assemble the molds, and remove the molds after curing in a standard curing box for 24 hours. Test the shrinkage performance after curing for 1 day to 180 days, and the compressive strength and tensile properties after curing for 28 days.

[0091] The entire process of preparation steps 1), 2), 3) and 4) takes 10 minutes.

[0092] Comparative Example

[0093] The comparative example cites "Example 2" in the patent "An ecological high-ductility, low-shrinkage cement-based composite material and method prepared using coal gangue as aggregate" (application number 202410907273.8), and its formulation is shown in Table 8.

[0094] Table 8 Material Proportion (Mass Ratio)

[0095]

[0096] The cement is P·I cement, the particle size of the coal gangue fine aggregate is 0.06-1.18 mm, and the fineness modulus is 1.60; the sulfur content of the coal gangue used is 0.8%, which belongs to low-sulfur coal gangue; the shrinkage reducing admixture is a composite of ethylene glycol diethyl ether liquid shrinkage reducing agent and super absorbent resin; the fiber is polypropylene fiber, the length is 10 mm, the elastic modulus is 35 GPa, and the tensile strength is 1200 MPa; the water reducer is a liquid polycarboxylic acid water reducer.

[0097] The preparation method of the ecological high-ductility low-shrinkage cement-based composite material comprises the following steps:

[0098] 1) Cement, fly ash and coal gangue fine aggregate are slowly stirred, that is, the rotation speed is 140 rpm and the revolution speed is 62 rpm, and the stirring is carried out for 3 minutes;

[0099] 2) Add water and stir rapidly, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm, and stir for 3 minutes;

[0100] 3) Add the water-reducing agent and stir rapidly, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm, and stir for 1 minute;

[0101] 4) Add shrinkage reducing agent and super absorbent resin and stir rapidly, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm, and stir for 3 minutes;

[0102] 5) Add the fiber and stir rapidly, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm, and stir for 3 minutes;

[0103] 6) Install the mold, remove the mold after curing in a standard curing room for 24 hours, and conduct shrinkage and mechanical property tests after curing for 28 days.

[0104] The entire process of preparation steps 1) to 6) takes 13 minutes.

[0105] The deformation properties, compressive strength, ultimate elongation and average crack width of the materials in Examples 1 to 5 and the comparative examples are shown in Table 9. Analyzing the deformation properties, the deformation of the all-solid waste high-ductility, low-shrinkage geopolymer concrete in Examples 1 to 5 after 28 days and 180 days of curing is basically within 600με, which shows the relative stability of the deformation properties of the all-solid waste high-ductility, low-shrinkage geopolymer in the examples, while the ecological high-ductility, low-shrinkage cement-based composite material in the comparative example is within 600με after 28 days of curing, but the deformation properties after 180 days are not tested. Analyzing the compressive strength, the compressive strength in the examples is above 35MPa, which can be used in the fields of construction and roads and bridges. Analyzing the ultimate elongation, the ultimate elongation of the all-solid waste high-ductility, low-shrinkage geopolymer concrete in Examples 1 to 5 is improved relative to the ultimate elongation in the comparative example as shown in Table 10. The ultimate elongation of the high-ductility, low-shrinkage geopolymer concrete prepared using all-solid waste is higher. The average crack width is analyzed, and the average crack width of the high ductility and low shrinkage geopolymer concrete prepared by using all-solid waste is within 200 μm, which meets the high ductility requirements. The data analysis in Table 9 shows the feasibility of replacing cement with geopolymer, using solid waste aggregate, adding shrinkage reducers and expansion agents, etc. to prepare all-solid waste high ductility and low shrinkage geopolymer concrete.

[0106] Table 9 Deformation properties, compressive strength, ultimate elongation and average crack width of high ductility and low shrinkage concrete in Examples 1 to 5 and Comparative Examples

[0107]

[0108] Note: Deformation with “-” indicates contraction, and without “-” indicates expansion deformation

[0109] Table 10 The improvement effect of the ultimate elongation of all-solid waste high ductility low shrinkage geopolymer concrete in Examples 1 to 5 relative to the ultimate elongation in the comparative example

[0110]

[0111] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be thought of by a person skilled in the art within the technical scope disclosed by the present invention without creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.

Claims

1. A high-ductility, low-shrinkage geopolymer concrete material made from all solid waste, characterized in that: The method comprises the following raw materials in proportions by mass: 615-1230 parts of coal gangue powder, 0-615 parts of fly ash, 123-492 parts of alkali activator, 369-443 parts of fine aggregate, 24.6-98.4 parts of shrinkage reducing agent, 12.3-24.6 parts of water reducing agent, 6.15-12.3 parts of hydroxypropyl methylcellulose, 369-418 parts of water and 19.5-26 parts of fiber.

2. The all-solid waste high ductility low shrinkage geopolymer concrete material according to claim 1, characterized in that: The specific surface area of ​​the coal gangue powder and fly ash is not less than 664m 2 / kg, and the basic particle size is 0.7~40μm; the total mass content of aluminum oxide and silicon oxide in the coal gangue powder and fly ash is not less than 90%.

3. The all-solid waste high ductility and low shrinkage geopolymer concrete material according to claim 1, characterized in that: The alkaline activator is one or a combination of water glass and sodium hydroxide; the modulus of water glass is 1.8-3.

3.

4. The all-solid waste high ductility low shrinkage geopolymer concrete material according to claim 1, characterized in that: The fine aggregate is one of coal gangue fine aggregate and recycled fine aggregate or a combination thereof, the maximum particle size of the fine aggregate is 1.18 mm, and the fineness modulus is 1.36-1.

58.

5. The all-solid waste high ductility low shrinkage geopolymer concrete material according to claim 1, characterized in that: The shrinkage reducing agent is one or a combination of ethylene glycol diethyl ether liquid shrinkage reducing agent and ettringite expansion agent.

6. The all-solid waste high ductility low shrinkage geopolymer concrete material according to claim 1, characterized in that: The fiber is polyvinyl alcohol fiber, with a diameter of 25-40 μm, a length of 8-12 mm, an elastic modulus of 34-36 GPa, a tensile strength of at least 1200 MPa, and an ultimate elongation of 9-12%.

7. The method for preparing the all-solid waste high ductility and low shrinkage geopolymer concrete material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Stir the gangue powder and fly ash slowly in a mixer for 1-2 minutes, with the rotation speed of 140 rpm and the revolution speed of 62 rpm; 2) Add the alkaline activator and water into the mixer and stir rapidly for 3-4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm; 3) Add fine aggregate, shrinkage reducing agent, water reducing agent and hydroxypropyl methylcellulose and stir rapidly for 3-4 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm; 4) Add the fiber and stir rapidly for 2-3 minutes, i.e., the rotation speed is 285 rpm and the revolution speed is 125 rpm; 5) Assemble the mold, cure in a standard curing box for 24 hours, then remove the mold and test the deformation performance, compressive strength and tensile properties.

8. The method for preparing the all-solid waste high-ductility low-shrinkage geopolymer concrete material according to claim 7, characterized in that: The following steps are involved: The entire process of preparation steps 1), 2), 3) and 4) takes 9 to 13 minutes.

Citation Information

Patent Citations

  • Ecological high-ductility low-shrinkage cement-based composite material prepared from coal gangue as aggregate and method

    CN118851669A

Cited By

  • Low-carbon low-shrinkage high-ductility solid waste concrete and preparation method thereof

    CN121974615A